2019
DOI: 10.14238/pi59.4.2019.169-74
|View full text |Cite
|
Sign up to set email alerts
|

Predictive factors of ketoacidosis in type 1 diabetes mellitus

Abstract: Background Diabetic ketoacidosis (DKA) is an acute complication in type 1 diabetes mellitus (DM) and a significant cause of morbidity and mortality in developing countries. Diabetic ketoacidosis can be prevented by good management of the disease. Risk factors from previous studies that increase the DKA incidence were peripubertal age, female gender, low socio-economic status, low parental education status, DKA at the first diagnosis of type 1 DM, infection, psychological problems, poor metabolic control, and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Based on medical record data from RSUP dr. Sardjito in Yogyakarta, it was found that the Dela Serlina/KESANS Diabetic Ketoacidosis prevalence of DKA in the 2014-2016 period was 62.5%. (Listianingrum, Patria, and Wibowo 2019)…”
Section: A Epidemiologymentioning
confidence: 99%
“…Based on medical record data from RSUP dr. Sardjito in Yogyakarta, it was found that the Dela Serlina/KESANS Diabetic Ketoacidosis prevalence of DKA in the 2014-2016 period was 62.5%. (Listianingrum, Patria, and Wibowo 2019)…”
Section: A Epidemiologymentioning
confidence: 99%
“…4 Compared to developed countries which is only 0.15 -0.31%, mortality related to DKA in developing countries is quite high, namely 3.4 -13.4%. 4 In 2017, 71% of children with DMT1 were first diagnosed with DKA. 4 This figure increased between 2015 and 2016 which was around 63%.…”
Section: Introductionmentioning
confidence: 97%
“…1 Diabetic ketoacidosis (DKA) is one of the acute complications of DMT1. 4 This situation causes significant morbidity and mortality in people with DMT1. 4 Compared to developed countries which is only 0.15 -0.31%, mortality related to DKA in developing countries is quite high, namely 3.4 -13.4%.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations